Three pairs of fungal Trametes strains isolated from distinct geographic origins show conserved genomic features and adaptive response to plant biomass - E. Drula; D. Navarro; J. Lambert; D. Chaduli; A. Lomascolo; C. Heilmann; S. Grisel; K. Barry; K. Labutti; B. Andreopoulos; L. Siyoun; S. Tejomurthula; et al. (Bioresource Technology, 2026)

Mapping benthic marine habitats featuring coralligenous bioconstructions: a new approach to support geobiological research - Giuseppe Maruca; Mara Cipriani; Rocco Dominici; Gianpietro Imbrogno; Giovanni Vespasiano; Carmine Apollaro; Francesco Perri; Fabio Bruno; Antonio Lagudi; Umberto Severino; Valentina A. Bracchi; Daniela Basso; et al. (Ocean Science, 2025)
Seabed mapping represents a very useful tool for seascape characterization and benthic habitat study and requires advanced technologies for acquiring, processing, and interpreting remote data. Particularly, acoustic instruments, such as high-resolution swath bathymetry sounders (i.e., multibeam echosounder: MBES), allow us to recognize, identify, and map the extension of benthic habitats without applying invasive mechanical procedures. Bathymetry and backscatter (BS) data are crucial to perform modern habitat mapping. Although the acquisition and processing of bathymetric data follow standardized procedure (e.g., Hydrographic Organization guidelines), and recent studies have proposed recommendations for backscatter acquisition and processing, a broadly validated methodological approach, integrating geomorphometric analysis for benthic habitat mapping, is still lacking. In this work, a new approach for benthic habitat mapping, with a focus on coralligenous bioconstructions, was developed using the open-source software QGIS. This methodology, tested within the Isola Capo Rizzuto Marine Protected Area (Calabria, Italy), is designed to be freely reproducible by researchers working in the field of marine ecosystem monitoring and conservation. Through the proposed mapping procedure, it is possible to (i) identify benthic habitats in selected study areas by combining bathymetry and BS data with geomorphological indices performed in QGIS and (ii) quantitatively define the 2D and 3D distribution of coralligenous bioconstructions in terms of surface covered, thickness, and volume. Moreover, the statistical analysis of quantitative morphometric data allowed for comparison of geometric characteristics of different coralligenous morphotypes. The obtained results, combined with improvement of minimally invasive sampling and geobiological–geochemical characterization, can contribute to the development of protocols aimed at monitoring marine bioconstructed ecosystems, many of which are protected by national and international regulations due to their importance for Mediterranean biodiversity preservation, and plan actions for their protection and persistence.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Multiple provenance of inter-eruptive fluvial sandstones of the Albian Cerro Castaño Member, Patagonia - A. Martín Umazano; Pablo M. Villegas; Mauro I. Bernardi; Leandro J. Amodeo; Bruno C. Rosso (Journal of South American Earth Sciences, 2025)

Integration of satellite and aerial images with multichannel GPR surveys in the archaeological area of Augusta Bagiennorum for an improved description of the urban setting - A. Vergnano; P. de Vingo; G. Rosso; S. Uggè; C. Comina (Journal of Applied Geophysics, 2025)

Associations between toxicity-weighted concentrations and dementia risk: Results from the Cardiovascular Health Cognition Study - Breanna M. Crane; Kyle D. Moored; Patrick T. Donahue; Anne E. Corrigan; Frank C. Curriero; Timothy M. Shields; Michael R. Desjardins; Emily A. Richards; Andrea L. Rosso; Gina S. Lovasi; Michelle C. Odden; Oscar L. Lopez; et al. (Science of The Total Environment, 2024)

Alternative green solvents associated with ultrasound-assisted extraction: A green chemistry approach for the extraction of carotenoids and chlorophylls from microalgae - Andrêssa S. Fernandes; Patrícia A. Caetano; Eduardo Jacob-Lopes; Leila Queiroz Zepka; Veridiana Vera de Rosso (Food Chemistry, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Trophic ecology of common bottlenose dolphins in a pelagic insular environment inferred by stable isotopes - Ester Dias; Morgane Dromby; Rita Ferreira; Ágatha Gil; Raquel Tejerina; L. Filipe C. Castro; Massimiliano Rosso; Isabel Sousa-Pinto; Joel C. Hoffman; Maria A. Teodósio; Ana Dinis; Filipe Alves (Hydrobiologia, 2023)
The common bottlenose dolphin ( Tursiops truncatus ) is a top marine predator widely dispersed in coastal and pelagic habitats and with a generalist feeding behavior. Yet, information on the trophic ecology of animals inhabiting pelagic environments is still scarce. Using carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotope ratios, we identified and quantified the main groups of prey assimilated by bottlenose dolphins inhabiting an oceanic habitat (Madeira Island, East Atlantic). Bottlenose dolphins assimilated pelagic, schooling fish (such as blue jack mackerel, Trachurus picturatus ) and mesopelagic and demersal squids, which reinforces the pelagic dietary composition of insular/oceanic dolphins. Also, intra-seasonal differences were found in their stable isotope ratios, which suggest intraspecific variability in the feeding behavior among individuals living in the same area. Sex was not the main factor contributing to these differences, suggesting the lack of trophic niche segregation between adult males and females in this offshore environment. Nonetheless, further studies including different life stages and information on the ecophysiological requirements are necessary to disclose the factors responsible for the observed variability. This study showed that insular dolphins fed primarily on economically important pelagic prey, highlighting the need of developing management strategies that integrate conservation in fisheries plans.

Degradation of carbamazepine in surface water: performance of Pd-modified TiO2 and Ce-modified ZnO as photocatalysts - Lucía Rossi; Paula I. Villabrille; Damián J. Marino; Janina A. Rosso; Paula Caregnato (Environmental Science and Pollution Research, 2023)

A chromosome 16 deletion conferring a high sucrose phenotype in soybean - Alexandra Ostezan; Elizabeth M. Prenger; Luciana Rosso; Bo Zhang; Robert M. Stupar; Travis Glenn; M. A. Rouf Mian; Zenglu Li (Theoretical and Applied Genetics, 2023)

Preliminary data on ostracods and foraminifers living on coralligenous bioconstructions offshore Marzamemi (Ionian Sea, SE Sicily) - F. Sciuto; C. Altieri; D. Basso; F. D'Alpa; G. Donato; V.A. Bracchi; M. Cipriani; A. Guido; A. Rosso; R. Sanfilippo; D. Serio; A. Viola (Revue de Micropaléontologie, 2023)

Temporal variation of soil N supply defines N fixation in soybeans - Luiz H. Moro Rosso; André F. de Borja Reis; Santiago Tamagno; Adrian A. Correndo; P.V. Vara Prasad; Ignacio A. Ciampitti (European Journal of Agronomy, 2023)

The Antillean manatee ( Trichechus manatus manatus ) along the Caribbean coast of Colombia: underused incidental records help identify present and past coastal‐lowland hotspots - Adolphe O. Debrot; Dalila Caicedo‐Herrera; Isabel Gómez‐Camelo; Yenyfer Moná‐Sanabria; Camila Rosso; Jan Tjalling van der Wal; Antonio A. Mignucci‐Giannoni (Marine Mammal Science, 2023)

Multi-regional comparison of scarring and pigmentation patterns in Cuvier’s beaked whales - Frazer G. Coomber; Erin A. Falcone; Erin L. Keene; Gustavo Cárdenas-Hinojosa; Rodrigo Huerta-Patiño; Massimiliano Rosso (Mammalian Biology, 2022)

A new species of Hoplias malabaricus species complex ( Characiformes: Erythrinidae ) from the Crepori River , Amazon basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González‐Castro; Mendelsohn F. B. Souza; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Journal of Fish Biology, 2022)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral‐line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii‐iv, 7–8 anal‐fin rays, ii‐iv, 12–15 caudal‐fin rays, last vertical series of scales on the base of caudal‐fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species‐group by means of landmark‐based morphometrics and DNA Barcoding ( Cytochrome c Oxidase I gene ). An identification key to species of the H. malabaricus species complex is provided.

V-doped TiO2 photocatalysts and their application to pollutant degradation - Lucía Rossi; Magdalena Palacio; Paula I. Villabrille; Janina A. Rosso (Environmental Science and Pollution Research, 2021)

Effects of organic matter addition on chronically hydrocarbon‐contaminated soil - Rocío Medina; Pedro M. David Gara; Janina A. Rosso; María T. Del Panno (Biodegradation, 2021)

Correction to: Secondary metabolite gene clusters arrangement and conservation within the genome of Stemphylium lycopersici codes the pathways for the synthesis of specific and non-specific toxins - Rocio Medina; Mario E. E. Franco; César G. Lucentini; Janina A. Rosso; Mario C. N. Saparrat; Laura C. Bartel; Pedro A. Balatti (Australasian Plant Pathology, 2021)

Secondary metabolite gene clusters arrangement and conservation within the genome of Stemphylium lycopersici codes the pathways for the synthesis of specific and non-specific toxins - Rocio Medina; Mario E. E. Franco; César G. Lucentini; Janina A. Rosso; Mario C. N. Saparrat; Laura C. Bartel; Pedro A. Balatti (Australasian Plant Pathology, 2021)

Structure and distribution of fish assemblages at Burdwood Bank, the first Sub-Antarctic Marine Protected Area “Namuncurá” in Argentina (Southwestern Atlantic Ocean) - S. M. Delpiani; D. O. Bruno; D. M. Vazquez; F. Llompart; G. E. Delpiani; D. A. Fernández; J. J. Rosso; E. Mabragaña; J. M. Díaz de Astarloa (Polar Biology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Hydrological variability, zooplankton availability and the shift between planktivore-benthivore feeding behaviour in the visual predator fish, Odontesthes bonariensis - A. M. Rennella; M. D. Geronazzo; M. E. Romero; M. Boveri; J. J. Rosso (Environmental Biology of Fishes, 2019)

Nerve Growth Factor Role on Retinal Ganglion Cell Survival and Axon Regrowth: Effects of Ocular Administration in Experimental Model of Optic Nerve Injury - Louise A. Mesentier-Louro; Pamela Rosso; Valentina Carito; Rosalia Mendez-Otero; Marcelo F. Santiago; Paolo Rama; Alessandro Lambiase; Paola Tirassa (Molecular Neurobiology, 2019)

Real-time assays for detection of Phytophthora spp. and identification of an avr3a gene variant - Shimaa R. T. Tolba; Mariella M. Finetti Sialer; Laura C. Rosso; Mahmoud M. A. Moustafa; Chiara Ruggeri; Ibrahim I. S. El-Shawaf; Aurelio Ciancio (Journal of Plant Diseases and Protection, 2018)

Screening and identification of horticultural soil fungi for their evaluation against the plant parasitic nematode Nacobbus aberrans - Ana L. Sosa; Laura C. Rosso; Fabricio A. Salusso; Miriam G. Etcheverry; María A. Passone (World Journal of Microbiology and Biotechnology, 2018)

Cyclic tensile-compressive tests on thin concrete boundary elements with a single layer of reinforcement prone to out-of-plane instability - Angelica Rosso; Lisandro A. Jiménez-Roa; João Pacheco de Almeida; Aydee Patricia Guerrero Zuniga; Carlos A. Blandón; Ricardo L. Bonett; Katrin Beyer (Bulletin of Earthquake Engineering, 2018)

Combination of sunlight, oxidants, and Ce-doped TiO2 for phenol degradation - Marcela V. Martin; Adriana Ipiña; Paula I. Villabrille; Janina A. Rosso (Environmental Science and Pollution Research, 2017)

New Mediterranean Biodiversity Records (November, 2016) - CH. MYTILINEOU; E.H.Kh. AKEL; N. BABALI; P. BALISTRERI; M. BARICHE; Y.Ö. BOYACI; L. CILENTI; C. CONSTANTINOU; F. CROCETTA; M. ÇELİK; H. DERELI; C. DOUNAS; et al. (Mediterranean Marine Science, 2016)
In the present Collective Article information on 26 taxa belonging to 8 Phyla and extended from the western Mediterranean to the Levantine Sea are presented. The new records were found in 9 countries as follows: Spain: first record for the Mediterranean of the crab Cancer bellianus; Algeria: further records of the alien fish Lagocephalus sceleratus to the west Algerian waters; Italy: first report on the presence and establishment of the ctenophore Mnemiopsis leidyi in Lessina and Varano Lagoons (W. Adriatic) and of Penaeus aztecus in Corigliano Gulf (Italian Ionian). Moreover, the extension of the distribution range of the polychaete Branchiomma bairdi to W. Sicily as well as that of the crab Ocypode cursor and the bryozoan Catenicella paradoxa to E. Sicily are cited. Slovenia: the record of the rare saccoglossan gastropod Placida cremoniana from Piran (Gulf of Trieste) is the first for the Adriatic; Greece: the native sea slug Eubranchus farrani is the first from the Eastern Mediterranean; many sightings of the bamboo corals Isididae distributed along all the E. Ionian Sea and the establishment of P. aztecus in all Greek waters are also reported for first time; the westernmost extension of the alien urchin Diadema setosum in Cretan waters is cited and new sights of the alien species Goniobranchus annulatus and Pterois miles are shown. Turkey: the alien fish Champsodon capensis is reported for first time from the Aegean Sea and the native acari Agauopsis microrhyncha from the Levantine Sea; a new observation of the alien crab Atergatis roseus in Güllük Bay-Aegean is also mentioned; Cyprus: first records of the alien urchin D. setosum and Lobotes surinamensis in Cypriot waters; Lebanon: several sightings of Monachus monachus from the Lebanese waters indicate a potential better status of the species in the area, Egypt: first records of the alien crab Dorippe quadridens and the alien gastropods Nerita sanguinolenta and Conomurex persicus from the Mediterranean Egyptian waters; extension of the distribution range of Diodora funiculata and Diodora rueppellii and a second record of the alien Nerita sanguinolenta in the same area.

Bryozoan diversity in the Mediterranean Sea: an update - A. ROSSO; E. Di MARTINO (Mediterranean Marine Science, 2016)
This paper provides a current view of the bryozoan biodiversity of the Mediterranean Sea updating the checklist by Rosso (2003). Bryozoans presently living in the Mediterranean increase to 556 species, 212 genera and 93 families. Cheilostomes largely prevail (424 species, 159 genera and 64 families) followed by cyclostomes (75 species, 26 genera and 11 families) and ctenostomes (57 species, 27 genera and 18 families). Few families and genera make the bulk of this biodiversity whereas one third of families are monospecific. The number of species-rank taxa has increased by 81 in the last dozen years but most of these additions relate to the revision of material from old collections and to the introduction of non-indigenous species. Most of the bryozoan diversity is distributed in the coralligenous and dark and semi-dark cave biocoenoses followed by detritic bottoms. Diversity lowers in shallow-water vegetated bottoms and in bathyal habitats. Further increase in diversity is expected from investigation of still poorly known areas and habitats and the need for rapid assessment is remarked on in view of the management of Mediterranean habitats through the EU Marine Strategy Directive.

The influence of Ce doping of titania on the photodegradation of phenol - Marcela V. Martin; Paula I. Villabrille; Janina A. Rosso (Environmental Science and Pollution Research, 2015)

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Macro- and megafauna recorded in the submarine Bari Canyon (southern Adriatic, Mediterranean Sea) using different tools - G. D'ONGHIA; F. CAPEZZUTO; F. CARDONE; R. CARLUCCI; A. CARLUCCIO; G. CHIMIENTI; G. CORRIERO; C. LONGO; P. MAIORANO; F. MASTROTOTARO; P. PANETTA; A. ROSSO; et al. (Mediterranean Marine Science, 2015)
Macro- and megafauna were recorded in the submarine Bari Canyon (southern Adriatic Sea, Mediterranean Sea) during an oceanographic cruise carried out in May-June 2012 and an experimental fishing survey conducted in November 2013. During the former, a total of 20 benthic samples were taken using a Van Veen grab at depths between 268 and 770 m and 4 deployments of a baited lander, for about 43 hours of video records, were carried out at depths between 443 and 788 m. During the latter, 8 longline fishing operations were conducted from 338 down to 612 m. Eighty-five living benthic and benthopelagic species were recorded: 29 Porifera, 1 Cnidaria, 2 Mollusca, 11 Annelida, 1 Arthropoda, 19 Bryozoa, 3 Echinodermata and 19 Chordata. A total of 51 species are new records for the Bari Canyon, 29 new records for the Adriatic Sea. Among the Porifera Cerbaris curvispiculifer is a new addition for the Italian Sponge Fauna. The first certain record of living specimens for the bryozoan Crisia tenella longinodata is reported. A total of 6 Mediterranean endemic species have been identified: 4 Porifera and 2 Annelida. The bathymetric range of some species has been extended. New information acquired for deep sea species confirms their importance in the structure of cold-water coral communities. This study has updated the knowledge on the biodiversity of the Adriatic Sea, as well as of the Bari Canyon in particular, one of the sites designated as “jewels of the Mediterranean” for which urgent conservation measures are needed.

Complexity–entropy analysis of daily stream flow time series in the continental United States - Francesco Serinaldi; Luciano Zunino; Osvaldo A. Rosso (Stochastic Environmental Research and Risk Assessment, 2014)

Remediation of phenanthrene-contaminated soil by simultaneous persulfate chemical oxidation and biodegradation processes - Verónica C. Mora; Laura Madueño; Marina Peluffo; Janina A. Rosso; María T. Del Panno; Irma S. Morelli (Environmental Science and Pollution Research, 2014)

Pauling bond strength, bond length and electron density distribution - G. V. Gibbs; N. L. Ross; D. F. Cox; K. M. Rosso; B. B. Iversen; M. A. Spackman (Physics and Chemistry of Minerals, 2014)

Serpula aggregates and their role in deep-sea coral communities in the southern Adriatic Sea - R. Sanfilippo; A. Vertino; A. Rosso; L. Beuck; A. Freiwald; M. Taviani (Facies, 2013)

Isolation and identification of entomopathogenic fungi and their evaluation against Tribolium confusum, Sitophilus zeamais, and Rhyzopertha dominica in stored maize - P. Barra; L. Rosso; A. Nesci; M. Etcheverry (Journal of Pest Science, 2013)

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

Implications of alternative electron sinks in increased resistance of PSII and PSI photochemistry to high light stress in cold-acclimated Arabidopsis thaliana - A. G. Ivanov; D. Rosso; L. V. Savitch; P. Stachula; M. Rosembert; G. Oquist; V. Hurry; N. P. A. Hüner (Photosynthesis Research, 2012)

Water–sediment niche differentiation in ancient marine lineages of Exiguobacterium endemic to the Cuatro Cienegas Basin - Eria A. Rebollar; Morena Avitia; Luis E. Eguiarte; Andrea González‐González; Lucy Mora; Germán Bonilla‐Rosso; Valeria Souza (Environmental Microbiology, 2012)
Summary The evolutionary history and ecological differentiation of the genus Exiguobacterium was characterized within natural communities from the Cuatro Cienegas Basin, Mexico. Exiguobacterium comprises both halophilic and alkaliphilic bacteria that are abundant among the aquatic systems of the Cuatro Cienegas Basin. We obtained complete sequences of the 16srRNA gene and partial sequences of four housekeeping genes ( citC , rpoB , recA and hsp70 ) in 183 Exiguobacterium isolates retrieved from distinct aquatic systems. We defined three main phylogroups that are closely related to marine and thermophilic species of the genus. These phylogroups were neither specific to a given aquatic system nor to a particular salinity. Phylogenetic reconstruction indicated the presence of several small clusters within the phylogroups. These clusters consisted of isolates predominantly retrieved from sediment or water. Unifrac and AdaptML analyses confirmed this observation, pointing towards a clear pattern of differentiation linked to either sediment or water habitats. Our results are in line with the concept that niche differentiation is one of the main factors shaping prokaryotic populations and leading to evolutionary divergence.

Impairment of Erythrocytes Incubated in Glucose Medium: A Wavelet-Information Theory Analysis - A. M. Korol; O. A. Rosso; M. T. Martín; M. D’Arrigo; B. D. Riquelme (Cell Biochemistry and Biophysics, 2011)

Natural markings of Cuvier's beaked whale Ziphius cavirostris in the Mediterranean Sea - M Rosso; M Ballardini; A Moulins; M Würtz (African Journal of Marine Science, 2011)

Thioarsenides: a case for long-range Lewis acid–base-directed van der Waals interactions - G. V. Gibbs; A. F. Wallace; R. T. Downs; N. L. Ross; D. F. Cox; K. M. Rosso (Physics and Chemistry of Minerals, 2011)

Cobbles colonization pattern from a tsunami-affected coastal area (SW Thailand, Andaman Sea) - R. Sanfilippo; A. Rosso; D. Basso; D. Violanti; I. Di Geronimo; R. Di Geronimo; F. Benzoni; E. Robba (Facies, 2011)

Cortical maldevelopment in congenital cytomegalovirus infection transmitted by a woman with preexisting immunity - C Arpino; G Castelli Gattinara; M Rosso; A Pelliccia; G Fariello; P Curatolo (Journal of NeuroVirology, 2008)

A role for substance P in cancer promotion and progression: a mechanism to counteract intracellular death signals following oncogene activation or DNA damage - F. Esteban; M. Muñoz; M. A. González-Moles; M. Rosso (Cancer and Metastasis Reviews, 2006)

Pregnancy History and Incidence of Melanoma in Women: A Pooled Analysis - Margaret R. Karagas; Michael S. Zens; Therese A. Stukel; Anthony J. Swerdlow; Stefano Rosso; Anne Osterlind; Thomas Mack; Connie Kirkpatrick; Elizabeth A. Holly; Adele Green; Richard Gallagher; J. Mark Elwood; et al. (Cancer Causes & Control, 2006)

Rapid Affinity Purification Processes for Cyclodextrin Glycosyltransferase from Bacillus circulans - A. Rosso; S. Ferrarotti; M.V. Miranda; N. Krymkiewicz; B.C. Nudel; O. Cascone (Biotechnology Letters, 2005)

Electron density distribution and bond critical point properties for forsterite, Mg2 SiO4, determined with synchrotron single crystal X-ray diffraction data - A. Kirfel; T. Lippmann; P. Blaha; K. Schwarz; D. F. Cox; K. M. Rosso; G. V. Gibbs (Physics and Chemistry of Minerals, 2005)

Experimental and theoretical bond critical point properties for model electron density distributions for earth materials - G. V. Gibbs; D. F. Cox; K. M. Rosso; A. Kirfel; T. Lippmann; P. Blaha; K. Schwarz (Physics and Chemistry of Minerals, 2005)

Analysis of wavelet-filtered tonic-clonic electroencephalogram recordings - O. A. Rosso; A. Figliola; J. Creso; E. Serrano (Medical & Biological Engineering & Computing, 2004)

Wavelet entropy in event-related potentials: a new method shows ordering of EEG oscillations - R. Quian Quiroga; O. A. Rosso; E. Ba?ar; M. Schrmann (Biological Cybernetics, 2001)

Use of oligochaete communities for assessment of ecotoxicological risk in fine sediment of rivers and canals of the Artois-Picardie water basin (France) - J. Prygiel; A. Rosso-Darmet; M. Lafont; C. Lesniak; A. Durbec; B. Ouddane (Hydrobiologia, 1999)